Penerapan Metode Story Telling Menggunakan Media Kartu Ekspresi Untuk Meningkatkan Kemampuan Bersosialisasi - Revi Faradilah; Weni Kurnia Rahmawati; Nailul Fauziah (Universitas Hamzanwadi, 2026)
Mentally retarded students are students who experience difficulties in their cognitive and affective functions, affectively mentally retarded students experience difficulties in adaptive behavior, especially in the ability to interact between individuals. The formulation of the problem in this study is to improve socialization skills in students with mental retardation by applying the storytelling method using expression card media. The purpose of this study is to improve socialization skills in students with mental retardation by applying the storytelling method using expression card media. The research method uses single subject research (SSR), with 1 subject as a mentally retarded student at Harapan Pelangi Kalisat Special Needs School. This study applies an A-B design. A includes the basic phase while B is the intervention phase. The focus of the targeted behavior is social skills through the application of the storytelling method using expression cards as media. The data obtained were examined using analysis strategies within conditions and between conditions. The results of this examination indicate that the use of the storytelling approach with expression card tools results in a greater capacity for social engagement. In the baseline phase, student F obtained a value from the stability range of 5.4%, mean level 26%, upper limit 28.7% and lower limit 23.3%. In the intervention phase or after receiving treatment, student F showed a stability range value of 12%, with an average level of 72%, an upper limit of 78%, and a lower limit of 66%. The findings of this study are expected to provide benefits to teachers as a development of science in the field of special education and can be used as an alternative interesting learning method to help students with social skills problems.